Analisis Kepemimpinan, Motivasi dan Budaya Organisasi Terhadap Peningkatan Kinerja ASN BDK Banjarmasin - Surya Subur (Balai Diklat Keagamaan Banjarmasin, 2020)
This study aims to analyze the influence of Leadership Style, Motivation and Organizational Culture on improving Employee Performance at BDK Banjarmasin which is measured by the skills, nature and attitude of a leader in providing motivation and building an organizational culture to achieve the target and optimal work results. The analysis of the results in this study used quantitative methods, by testing the validity and reliability of the research instruments. Where as to test the hypothesis using the classic assumption test, F test, t -test, partial correlation coefficient test and multiple regression. The results of the F test show the value of Fcount > Ftable and the significant value of 0,000 < 0.05 at the level of trust α = 0.05. The results of the calculation of Fcount 42.011 with Ftable 1.98 mean that the independent variables X1, X2, and X3 simultaneously influence the dependent variable Y. The t-test results show the value of tcount for each independent variable is more than the value of t table. Calculation Leadership Style 2,993, 3,592 Motivation and Organizational Culture 4,566 with t-table value = 1,98 means that each independent variable partially influences the dependent variable. Similarly, simultaneously. From the partial correlation coefficient the Organizational Culture variable has the highest correlation coefficient, which is equal to 0.266, means that Organizational Culture is the most dominant variable affecting the employee performance variable(Y).